2021
DOI: 10.1021/acs.jpclett.0c03469
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic Interlayer Exciton in GeSe/SnS van der Waals Heterostructure

Abstract: Stacking two or more two-dimensional materials to form a heterostructure is becoming the most effective way to generate new functionalities for specific applications. Herein, using GW and Bethe–Salpeter equation simulations, we demonstrate the generation of linearly polarized, anisotropic intra- and interlayer excitonic bound states in the transition metal monochalcogenide (TMC) GeSe/SnS van der Waals heterostructure. The puckered structure of TMC results in the directional anisotropy in band structure and in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…They also mitigate the viability of charge carrier recombination by reducing the distance required for photogenerated electrons and holes for reaching the active sites. Among 2D materials, transition metal chalcogenides 4,5 , and carbon nitrides 6,7 have been widely investigated. The other notable 2D materials to exhibit promising photocatalytic properties are the 2D layered double hydroxides (LDHs) 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…They also mitigate the viability of charge carrier recombination by reducing the distance required for photogenerated electrons and holes for reaching the active sites. Among 2D materials, transition metal chalcogenides 4,5 , and carbon nitrides 6,7 have been widely investigated. The other notable 2D materials to exhibit promising photocatalytic properties are the 2D layered double hydroxides (LDHs) 8,9 .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we carried out the Bethe−Salpeter equation (BSE) calculations on top of G0W0 in order to get the information on excitonic effects in the optical absorption using the Tamm-Dancoff approximation. 68 The frequency dependent macroscopic dielectric function by BSE is given by the equation 69…”
Section: ■ Methodsmentioning
confidence: 99%
“…The frequency dependent macroscopic dielectric function by BSE is given by the equation where φ cv S and E S are the excitonic wave function and energy, respectively for the excitonic state S. is the polarization vector and is the velocity operator between conduction and valence energy state. The BSE only give the information on direct transition.…”
Section: Methodsmentioning
confidence: 99%
“…Maity et al demonstrated that GeSe/SnS van der Waals heterostructures can produce linear polarization and interlayer exciton binding states. Also, the control of such interlayer exciton energies could enable their application in optoelectronics and optical quantum computers …”
Section: Introductionmentioning
confidence: 99%
“…18 interlayer exciton energies could enable their application in optoelectronics and optical quantum computers. 19 GaN is very suitable for gas sensors due to its excellent electronic properties. 20−22 For example, when Ga 12 N 12 nanoclusters are used as gas sensors for the detection of NO, NO 2 , and HCN, they exhibit an outstanding sensing performance.…”
Section: ■ Introductionmentioning
confidence: 99%